HASIL BELAJAR DAN PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) - Jasdilla, Loli; Kuswendi, Uus; Ramdhani, Sony (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The objectives of this research is to improve social science outcomes by using Think Pair Share (TPS) for the fourth grade in elementary school. This research is classroom action research. The procedure of this research conducted planning, acting, observation, and reflection. Subject of this research was 22 students for the fourth grade in SD 20 Kalumbuk, Padang. Techniques of collecting data were using test and observation. Data analyzed by using thematic analysis. Data validated by using triangulation, member checking, and reflecivity. The students’ learning outcomes improved from 76,75% into 89,67% (very good). The result of this research shows that cooperative model of Think Pair Share (TPS) type can improve social science outcomes for the fourth grade students of elementary school.